2018
DOI: 10.1002/uog.19039
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of diagnostic accuracy of early screening for pre‐eclampsia by NICE guidelines and a method combining maternal factors and biomarkers: results of SPREE

Abstract: Objective To test the hypothesis that the performance of first-trimester screening for pre-eclampsia (PE) by a method that uses Bayes' theorem to combine maternal factors with biomarkers is superior to that defined by current National Institute for Health and Care Excellence (NICE) guidelines.Methods This was a prospective multicenter study (screening program for pre-eclampsia (SPREE)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
323
1
15

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 275 publications
(358 citation statements)
references
References 30 publications
19
323
1
15
Order By: Relevance
“…The performance of the combined screening model used for the ASPRE trial (maternal factors, mean arterial pressure, mean uterine artery PI, PlGF) was practically identical when applied to the dataset used for its development and the actual clinical trial 9,76 . In fact, this screening model was found to be considerably more efficient for the prediction of early PE than were the history-based screening policies recommended by both the American College of Obstetricians and Gynecologists and the UK National Institute for Health and Care Excellence 22,86 .…”
Section: Recommendationsmentioning
confidence: 95%
See 1 more Smart Citation
“…The performance of the combined screening model used for the ASPRE trial (maternal factors, mean arterial pressure, mean uterine artery PI, PlGF) was practically identical when applied to the dataset used for its development and the actual clinical trial 9,76 . In fact, this screening model was found to be considerably more efficient for the prediction of early PE than were the history-based screening policies recommended by both the American College of Obstetricians and Gynecologists and the UK National Institute for Health and Care Excellence 22,86 .…”
Section: Recommendationsmentioning
confidence: 95%
“…A 2008 meta‐analysis indicated that increased PI, alone or combined with notching, is the most predictive Doppler index for PE. A considerable amount of evidence published since then indicates the superiority of mean uterine artery PI as the preferred Doppler index for PE screening, and this is the index used for screening and prevention in the first trimester.…”
Section: Screening For Pre‐eclampsia Using Ultrasoundmentioning
confidence: 99%
“…Second, 2999 twin pregnancies (validation dataset) that were examined at five hospitals in England (King's College Hospital and Medway Maritime Hospital, between December 2015 and April 2018; Homerton University Hospital, between January 2014 and April 2018; North Middlesex University Hospital, between May 2015 and April 2018; and Southend University Hospital, between June 2015 and April 2018), one hospital in Bulgaria (Dr. Shterev Hospital in Sofia, between January 2013 and April 2018) and one hospital in Spain (Hospital Clínico Universitario Virgen de la Arrixaca in Murcia, between March 2009 and April 2018). Third, the validation dataset of 16 747 singleton pregnancies from the Screening ProgRamme for prE‐Eclampsia (SPREE) study; this was a prospective multicenter study in seven National Health Service (NHS) maternity hospitals in England. This study was approved by the NHS Research Ethics Committee in England and the Hospital Ethics Committees of the participating hospitals in Bulgaria and Spain.…”
Section: Methodsmentioning
confidence: 99%
“…The authors of a prospective multicentre study published in Ultrasound in Obstetrics & Gynecology said that using this alternative method could double the detection rate of preterm pre-eclampsia 1. When pre-eclampsia leads to preterm birth before 37 weeks’ gestation the risk for complications is particularly high.…”
mentioning
confidence: 99%